Novel synthesis of CNTs–Si3N4/Cu nanocomposites: electroless deposition, powder metallurgy, spark plasma sintering, microstructure, and physical properties - Daoush, Walid M.; Inam, Fawad; Hong, Soon H.; Olevsky, E.; German, Randall M. (Frontiers in Materials, 2025)
IntroductionMetal matrix composites reinforced with ceramic and carbon nanotubes (CNTs) are considered recently as new materials for thermal managements and heat sink applications of electronic components.MethodCu nanocomposites reinforced with CNTs and different content of Si3N4 up to 5 wt.% (CNTs-xSi3N4/Cu) are synthesized by electroless Cu deposition process. The produced (CNTs-xSi3N4/Cu) nanocomposites powder were divided into two groups of samples. The first group were consolidated by two steps of cold pressing at 600 MPa compaction pressure followed by sintered under Ar atmosphere at 850°C for 90 min. However, the second group of powders are spark plasma sintered (SPS) under vacuum by simultaneously applying compaction pressure of 50 MPa at sintering temperature of 850°C for one min. The microstructure and the chemical composition of the investigated CNTs and the produced CNTs-xSi3N4/Cu powders as well as the CNTs-xSi3N4/Cu sintered nanocomposites were investigated by FTIR, SEM, TEM, EDX, X-ray mapping and XRD. The sinterability of the produced CNTs-xSi3N4/Cu nanocomposites is evaluated by measuring the Archimedes’ density and the coefficient of thermal expansion (CTE).Results and discussionThe electroless coating process enhancing the homogeneous distribution of CNTs and Si3N4 reinforced particles in the Cu matrix by preventing the formation of the agglomerations and segregations in the Cu matrix and retaining the nanostructure. The density and the CTE of the obtained CNTs-xSi3N4/Cu nanocomposites were improved by consolidation with SPS. The CNTs-xSi3N4/Cu nanocomposites sintered by SPS process have higher relative density approaches 100 % and lower CTE of 1.8 × 10−5°C-1–1.6 × 10−5°C-1 than, the density of the CNTs-xSi3N4/Cu nanocomposites sintered by conventional powder metallurgy technique with relative sintered density approaches 85 % and CTE of 2.6 × 10−5°C-1–1.9 × 10−5°C-1. Our findings owing that; the produced CNTs-Si3N4/Cu nanocomposites are expected as suitable candidate materials for thermal managements and heat sink packaging materials of electronic components.